Efficient synthesis of furfurylamine from biomass via a hybrid strategy in an EaCl:Gly–water medium - He, Wei; He, Yu-Cai; Ye, Jianren (Frontiers in Bioengineering and Biotechnology, 2023)
The objective of this work was to develop an efficient approach for chemoenzymatically transforming biomass to furfurylamine by bridging chemocatalysis and biocatalysis in a deep eutectic solvent of EaCl:Gly–water. Using hydroxyapatite (HAP) as support, heterogeneous catalyst SO42−/SnO2–HAP was synthesized for transforming lignocellulosic biomass into furfural using organic acid as a co-catalyst. The turnover frequency (TOF) was correlated with the pKa value of the used organic acid. Corncob was transformed by oxalic acid (pKa = 1.25) (0.4 wt%) plus SO42−/SnO2–HAP (2.0 wt%) to produce furfural with a yield of 48.2% and a TOF of 6.33 h-1 in water. In deep eutectic solvent EaCl:Gly–water (1:2, v/v), co-catalysis with SO42−/SnO2–HAP and oxalic acid was utilized to transform corncob, rice straw, reed leaf, and sugarcane bagasse for the production of furfural with the yield of 42.4%–59.3% (based on the xylan content) at 180°C after 10 min. The formed furfural could be efficiently aminated to furfurylamine with E. coli CCZU-XLS160 cells in the presence of NH4Cl (as an amine donor). As a result of the biological amination of furfural derived from corncob, rice straw, reed leaf, and sugarcane bagasse for 24 h, the yields of furfurylamine reached >99%, with a productivity of 0.31–0.43 g furfurylamine per g xylan. In EaCl:Gly–water, an efficient chemoenzymatic catalysis strategy was employed to valorize lignocellulosic biomass into valuable furan chemicals.